The Effect Of Potato Flour Substitution On The Quality Of Snow's Cookies - Ghifari, Muhammad Al; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This research is motivated by the lack of utilization of local food ingredients, especially potato starch in food processing. The main ingredient in making Snow White cookies is wheat flour which is still imported. This study aims to analyze the quality (shape, color, aroma, texture and taste) of snow white cookies substituted with potato flour as much as 25%, 50% and 75%. This type of research is a pure experiment with Completely Randomized Design (CRD) method. The data used are primary data obtained directly from 3 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of the potato flour snow princess cookies. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The results showed that potato flour substitution had an effect on color quality, while for the quality of shape, aroma, texture and taste there was no significant effect. The results of the test for the quality of the snow princess cookies were the best potato flour in the X1 treatment with 25% potato flour substitution.